Eficácia e segurança da reconstrução de mama com implante no carcinoma de mama localmente avançado: um estudo caso-controle pareado - Ribeiro, Luciana Machado [UNIFESP] (2020)
Background: Immediate implant-based breast reconstruction (IBBR) is rarely performed in patients with locally advanced breast carcinoma (LABC). It has not been considered the best indication, and the literature is scarce about this subject. Patients and Methods: A retrospective matched case-control study was performed in patients with LABC submitted to neoadjuvant chemotherapy (NCT). Forty-eight patients undergoing immediate IBBR were matched with 96 patients undergoing conventional mastectomy. Patients were matched according to 2 models based on prognostic characteristics prior to NCT (model 1) and response to NCT (model 2). Local recurrence and disease-free survival were compared between the groups. In the IBBR group, local complications were evaluated. Results: In all, 196 patients were evaluated. The mean tumour size of IBBR patients was 5.8 cm and 85,4% (41/48) had clinical stage III. At a mean follow-up of 74.7 months, the local recurrence rate was 6.2% (3/48), 15.6% (15/96) and 13.7% (13/95) in the IBBR, model 1 and model 2 groups, respectively (p > 0.05). Disease-free survival was higher in the IBBR group than in the model 1 group (mean 88.8 vs. 73.7 months; p = 0.05). In the group submitted to IBBR, 14.6% (7/48) of patients presented loss of prosthesis and 48.8% (20/41) developed capsular contracture. Conclusion: Immediate IBBR may be a safe and effective surgical procedure in selected patients with LABC.